20% chance of rain exploring the concept of risk - Jones, Richard B. (Richard Bradley), 1947- (Wiley, 2012)
"There are plenty of books on specialized risk topics but few that deal with the broad diversity and daily applicability of this subject. Risk applications require a robust knowledge of many attributes of this seemingly simple subject. This book teaches the reader through examples and case studies the fundamental (and subtle) aspects of risk - regardless of the specific situation. The text allows the reader to understand the concept of risk analysis while not getting too involved in the mathematics; in this method the reader can apply these techniques across a wide range of situations.The second edition includes new examples from NASA and several other industries as well as new case studies from legal databases. The many real-life discussion topics enable the reader to form an understanding of the concepts of risk and risk management and apply them to day-to-day issues"--